(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2015)
This paper presents results of experimental studies carried out with a Mather type plasma focus device of 2.2 kJ energy. A critical effect of plasma focus inner electrode, IE length on the plasma focus action is detected for IE length has been changed to 9.5, 10.5 and 11.5 cm respectively; also for different Argon gas pressure ranging from 0.2 to 1.8 Torr. To verify this effect, it is important to investigate the plasma focus characteristics such as, a focusing time, voltage spike amplitude, focus action intensity, focus duration time, plasma focus inductance, and radius of plasma focus column as well as pinching ratio. The diagnostics used in the experiments include a Rogowski coil and resistive high voltage probe to measure the discharge current and voltage signals respectively. All the results illustrated that, the best focus action has been achieved for IE length of 10.5 cm and at filling Argon gas pressures varied from 0.8 to 1.2 Torr.